Question
upstudy study bank question image url

Solve the following equation, and check the solution. \[ 5 x-2=6 x \]

Ask by Ray Johnson. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( x = -2 \)

Solution

Solve the equation \( 5x-2=6x \). Solve the equation by following steps: - step0: Solve for \(x\): \(5x-2=6x\) - step1: Move the variable to the left side: \(5x-2-6x=0\) - step2: Subtract the terms: \(-x-2=0\) - step3: Move the constant to the right side: \(-x=0+2\) - step4: Remove 0: \(-x=2\) - step5: Change the signs: \(x=-2\) The solution to the equation \(5x-2=6x\) is \(x=-2\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the equation \( 5x - 2 = 6x \), we first want to isolate the variable \( x \). 1. Subtract \( 5x \) from both sides: \[ -2 = 6x - 5x \] which simplifies to: \[ -2 = x \] Now, we have found \( x = -2 \). Next, let's check this solution by substituting \( x \) back into the original equation: For \( x = -2 \): \[ 5(-2) - 2 = 6(-2) \] Calculating both sides: \[ -10 - 2 = -12 \quad \text{and} \quad -12 = -12 \] Since both sides are equal, the solution \( x = -2 \) is correct!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy